Art, Heart, and Pedagogy for Social Change - Elizabeth Brule; Katya Kredl; Juliette Vaillancourt; Elise Zhao (Studies in Social Justice)
This article is a collective discussion with undergraduate students about their work in a second-year gender studies course. The discussion shares how active engagement in collective art production for social change can provide the seeds for decolonial, anti-racist and anti-ableist pedagogical practice. The course encourages students to actively engage in the classroom, raise questions and concerns about social justice, and implement ways to challenge social relations of power. Students work collectively on projects using a range of alternative ways of knowing, including sensory, heart, intellectual, and spiritual knowledge, to connect with the course material in creative ways. The article is a conversation with three students in the course and the work they produced. They discuss the various mediums they used, including poetry, collaging, and a case study of artists’ street art. The students touch on the politics of joy, self-care, heart knowledge, politics of suffering, and accessibility, illustrating how combining art with various ways of knowing has helped them develop deeply analytic, compassionate, and relational work for social change. The work affirms ways of knowing that have often evolved outside the colonial academic institution. The anti-racist, anti-colonial, anti-ableist, feminist and Indigenous pedagogies used in the course help to pluralize constructive capacities for more decolonizing, equitable, inclusive, anti-racist and expansive educational futures.